The Only Woman in the Room: Oral Histories of Senior Women Physicians in a Midwestern City - Anne Walling; Kari Nilsen; Kimberly J. Templeton (Mary Ann Liebert, 2020)
Introduction: The female students of the 1960s and 1970s have been at the forefront of issues for women in medicine throughout their careers. They have personally experienced the diverse challenges and opportunities that have continued to arise, for women in medicine over the past 50 years. Capturing their stories can provide a unique contribution to the history of women in medicine, especially in documenting the crucial transitional decades during which women entered the profession in increasing numbers. Their experiences can also inform programs to improve the careers of current and future women in medicine. Materials and Methods: We partnered with the Medical Society of Sedgwick County to invite all women who had been members before 1990 and still lived in the area to participate in focus groups about their experiences in medical school and residency. Interviews were recorded, and the recorded discussions and field notes were analyzed by using a thematic analysis approach Results: Discussions revolved around several topics, including motivations to become a physician, family attitudes, experiences during medical school and residency, and experiences with co-workers and patients. Illustrative quotes were selected for the themes identified. Discussion: This project illuminates the motivations, attitudes, and experiences of a diverse group of women who entered medical school in the 1960s and 1970s. Although they came from very different backgrounds and trained in a variety of institutions and specialties, their stories revealed consistent themes, many of which remain relevant for female physicians. Conclusion: This unique cohort of women were part of the major transition from times when women were rare in medicine to being at least half of physician trainees. Their experiences should be used to inform the profession moving forward.